Cape Verde : Poverty Reduction Strategy Paper; First Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2006)
This report summarizes the First Annual Progress Report on the Poverty Reduction and Growth Strategy (PRGS) program. It assesses the status of the strategy implementation and monitoring mechanism, and emphasizes the need to face enormous development challenges and curb poverty and unemployment. It reviews the agenda of structural reforms and also lists the sectoral achievements toward the five strategic aims. It provides a brief description of the monitoring and evaluation mechanisms for implementation in some sectors.